2016
DOI: 10.1159/000446844
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration and Its Risk Factors in North Africans Living in Algeria and Italy

Abstract: Purpose: To determine the risk factors for age-related macular degeneration (AMD) in Algerians, and compare these data with those on North Africans living in Italy. Methods: All patients over 55 years of age consulting one of the 23 involved Algerian ophthalmologists were invited to participate, and 1,183 patients were included. Data collection was standardized based on the Simplified Théa Risk Assessment Scale (STARS) questionnaire. A similar study was conducted in North Africans living in Italy (n = 1,011). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…A total of 8 studies assessed sunlight exposure levels based on time spent outdoors [14, 18, 2022, 24, 26, 27], 5 studies were based on occupational exposure to sunlight [14, 19, 20, 25, 27], 2 studies were based on living in a sunny region or sunny climate [16, 20], 3 studies were based on calculated doses of sunlight or blue light [15, 23, 25], and 6 studies were based on avoidance of the sun. [16, 17, 2325, 27]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8 studies assessed sunlight exposure levels based on time spent outdoors [14, 18, 2022, 24, 26, 27], 5 studies were based on occupational exposure to sunlight [14, 19, 20, 25, 27], 2 studies were based on living in a sunny region or sunny climate [16, 20], 3 studies were based on calculated doses of sunlight or blue light [15, 23, 25], and 6 studies were based on avoidance of the sun. [16, 17, 2325, 27]…”
Section: Resultsmentioning
confidence: 99%
“…Assessments and definitions of AMD varied among the studies. Standardized criteria for diagnosis of AMD were used in some studies [1517, 21, 22, 24–27], while in others, cases were diagnosed medically by an ophthalmologist or medical record review to identify the case [14, 1820, 23]. Two stages of AMD (early and late) were analyzed separately in 7 studies [17, 2023, 25, 27].…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies on Europe and America, and relatively few studies on Asia [ 10 , 22 , 31 ] and Africa [ 12 ]. Lazreg et al [ 12 ] found in a cross-sectional study of North Africans living in Algeria and Italy that patients with cataract surgery are more likely to have AMD than those who have not had surgery (OR: 2.69; 95% CI 1.96–3.70; p < 0.0001). Darker irises are also related to AMD, and it may affect the relationship between the surgery and AMD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 8 11 ], including systematic reviews [ 11 ], have not found a clear correlation between cataract surgery and AMD by comparing AMD patients with cataract surgery and those without AMD. A cross-sectional [ 12 ] study has explored this problem, but there are still no exact results.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that North-Africans living in Algeria had a lower risk for AMD than did North-Africans living in Italy, together with a generally healthier lifestyle (less obesity, smoking, cardiovascular diseases, and higher consumption of fruits and vegetables). 35 Adoption of Western lifestyle has been shown to be associated with increased risk of chronic diseases in many populations migrating from developing countries. 36 This new short questionnaire offers several advantages.…”
Section: Discussionmentioning
confidence: 99%